An adaptive multi-objective optimization method for optimum design of distribution networks. Issue 2 (1st February 2020) - Mohamadi, Mohamad Reza; Abedini, Mohammad; Rashidi, Bahram
ABSTRACT: The heat transfer search (HTS) algorithm is a metaheuristic algorithm inspired by the laws of thermodynamics. It has received attention from researchers in solving nonlinear problems in three phases, namely conduction, convection and radiation. However, there are some shortcomings in the use of this algorithm. Its inability to deal with multi-objective problems, coupled with the existence of search space limits and its lack of considering good characteristics of parents in the updating step of the conduction and radiation phases, make the applicability of HTS questionable. This article addresses such shortcomings by presenting an improved multi-objective heat transfer search algorithm (MOIHTS), which is capable of solving multi-objective problems while addressing the HTS updating problem. Pairwise comparison and crossing techniques are adopted to improve the accuracy of HTS and address the updating problem. The performance of the proposed algorithm is compared with a number of well-known algorithms.